Agricultural Self-efficacy Scale - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Improving women’s self-efficacy—that is, their belief in their capabilities to act effectively towards a goal—is an important and urgent policy goal. Despite being the sector that employs most of the labor force across the Global South, how to measure self-efficacy in agricultural activities in low-income countries remains understudied. This 10-item Agricultural Self-efficacy Scale allows us to capture the extent to which individuals believe in their own capacity to reach goals regarding different common activities in agriculture, grounded in McGee et al.’s (2009) framework for measuring entrepreneurial self-efficacy. This scale can be used to assess levels of agricultural self-efficacy in a population, determine which sub-domains of self-efficacy are strongest or weakest (e.g., managing labor or obtaining a loan) as well as to assess the impact of agriculture-related projects. This tool is suited for surveys run by NSOs, other nationally representative individual- or household-level surveys, and for targeted thematic or impact evaluation surveys designed to understand individuals' agency and decision-making. This data study includes following files. 1. A survey document (including implementation guidelines). 2. Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.